Truth or dare: can the mystery between different job demands and employee well-being and performance be solved? A conceptual framework and research agenda - Tabassum, R. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Occupational health and safety agencies have revealed that employees in human service sectors are particularly susceptible to experiencing high levels of psychological distress. While numerous scholars argue that acute job demands have adverse effects on employees' physical health and psychological well-being, previous studies have led to inconsistent findings regarding the impacts of chronic job demands on multiple work-related outcomes. Despite the wide-ranging interest in studying job demands, studies exploring the role of acute and chronic job demands on employees' psychological well-being and performance in high-demand and low-resource settings are mostly absent from the strategic human resource management (SHRM) literature. This review identifies the following three areas to narrow the gap in the SHRM literature: (a) highlight the individual as well as accumulated roles of acute and chronic demands on employee well-being and performance, (b) focus on the impact of acute and chronic job demands on employee well-being and performance with mediating mechanisms such as burnout and work engagement, and (c) the potential role of HPWSs that can moderate the adverse effects of acute and chronic job demands on employee outcomes. Furthermore, the proposed model facilitates a 'WellICBM being-Performance' enhancing workplace resulting from HPWSs in high-demand and low-resource settings.
Keywords: High-performance work systems, Jobs-Demands-Resources (JD-R) theory, psychological well-being, job performance, burnout and work engagement